Sorção de carbamazepina e lincomicina em biocarvão - Pegoraro, Thaisa (2015)
Biochar, also known as terra preta do índio, is a highly porous material and is a result of biomass pyrolysis in oxygen-controlled conditions and low temperatures (up to 600 oC). Due to the viable manufacturing process and the wide variety of applications, it is a promising material for various uses. Among the main uses of biochar, studies indicate its potential in improving soil quality, besides being a way of contributing to carbon sequestration from the atmosphere and used in the retention of organic and inorganic contaminants in the environment. This work aimed to present a review of the concepts and current studies on biochar, for a better understanding of the subject (Paper 1). The objective was to also investigate the adsorption of pharmaceuticals carbamazepine (CBZ) and lincomycin (LMC) by six biochars under the influence of surface characteristics of biochar (produced from Brazilian pepper and sugarcane bagasse, in temperatures of 300 o, 400 o and 600o C) and environmental factors (pH and adsorption competition between CBZ and LMC) (Paper 2). The latest study aimed to understand the effects of exposure of dissolved organic matter (DOM) in the surface properties of three biochars produced from sugarcane bagasse, in the CBZ adsorption (Paper 3). Batch equilibrium tests were performed in constant temperature, varying pH, and the data were adjusted in Freundlich isotherms. For the DOM test, the biochars were previously loaded with humic acid, tannic acid, gallic acid, and catechol in concentrations equivalent to those found in soils. The values of Kd, n and KF were reported and analyzed. As a result, it was found that biochars produced from sugarcane bagasse and high pyrolysis temperature were more effective in CBZ and LMC adsorption. In the biochar produced from bagasse at 300° C, the adsorption of CBZ was not affected by the presence of functional groups on the surface of biochar. LMC, which is ionized at pH 7.6, is more easily binded to negatively charged biochars when pH is acidic (pH<pKa). Furthermore, it was found that the CBZ and LMC compete for the same adsorption sites, regardless the variation of pH solution. In general, DOM affected adsorptive properties of biochars and attenuated CBZ adsorption, especially for biochars produced in higher temperatures because of the greater complexity of its structure, when DOM enters or blocks the biochar micro and mesoporous. It was concluded that the use of biochar as a product of sustainable feature looks promising, but there are still some gaps in the current literature about the positive and negative impacts of its use. Laboratory results indicate a possible use of biochar in removing organic compounds from water, which can replace less effective existing treatment technologies. There is to be considered, however, several factors that influence this process and more studies are needed to corroborate such evidence.